ASPEK PSIKOLOGI, SOSIAL-KULTURAL DAN SIKAP ISLAM TERHADAP PERILAKU TRANSEKSUAL DI INDONESIA - Widodo Winarso (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2015)
The aspect of social issues becomes one of the concerns of contemporary Islam. This aspect is usually discussed and became the hottest news in social life. One might feel having lack of unanimity in the provision of public attitudes towards him/her self. This is what happened to transsexual and genital surgery people. Those who have and do the things that feel cornered because people assume the actions carried out under the assumption that they have been violated. Transsexual is a person whose way of behaving not same to the appearance of gender roles in general. Transsexual is a person who in the various levels of